Analisis Realisasi Penyaluran Dana Kredit Usaha Rakyat Terhadap Produk Domestik Regional Bruto (Pdrb) Kabupaten/Kota Di Provinsi Kepulauan Bangka Belitung - Armaya, Armaya; Valeriani, Devi; Putra, Agung Riski (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2025)
This study aims to analyze and determine the Realization of the Distribution of People's Business Credit Funds consisting of Debtors, Contract Values and Outstandings on the Gross Regional Domestic Product of Regencies/Cities in the Bangka Belitung Islands Province in 2015-2023. This study uses a quantitative descriptive approach with secondary data. The analysis technique in this study uses panel data regression by selecting the most effective approach model so that the use of the Random Effect Model (REM). The results of the study indicate that Debtors have a positive and insignificant on the gross regional domestic product of regencies/cities in the Bangka Belitung Islands Province. The contract value has a positive and significant on the gross regional domestic product of regencies/cities in the Bangka Belitung Islands Province. Outstanding has a positive and significant on the gross regional domestic product of regencies/cities in the Bangka Belitung Islands Province.